Perencanaan Pembangunan dan Perhitungan Rencana Anggaran Biaya Gedung Aula di Kelurahan Selat Utara - Ronny Ananda; Fieka Febri Ayu Anggraeni; Putri Zahra Safira; Sanetyo Sugandanu; Jhon Farel Manurung; Eben Hezert Sihombing; Ferdy Aryo Yudistira; Goklas Kurniawan (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
Building and Impact Engineering (TMB) is a forum for implementing student learning outside the campus, which emphasizes the application of knowledge contextually through direct involvement in the community. This research was conducted in Selat Utara Village, Selat District, Kapuas Regency, with a focus on the planning of the construction of a hall building as a multifunctional public facility. The research method used is qualitative with data collection techniques through field observation and literature studies. The stages of the activity include coordination with the village, field surveys, primary data collection, community needs analysis, hall building design, preparation of working drawings, selection of material specifications, and calculation of the Budget Plan (RAB). The results of the activity are in the form of technical planning documents that include detailed working drawings, RAB, building design concepts, and field survey reports, which are expected to be initial recommendations for the village government in the physical construction of the hall building. The estimated total cost of the hall building construction is Rp. 1,108,349,000.00 with a unit price per square meter of Rp. 4,262,880.77. This activity not only provides real-life learning experiences for students, but also contributes to the development of village infrastructure, improving the quality of public services, and supporting the achievement of Sustainable Development Goals (SDGs) at the local level.